The State Sovereignty Issue in the European Union - Abrahamyan, Paytsar; Khachatryan, Ashot (ՀՀ ԳԱԱ)
The following article touches upon the issue of state sovereignty in the European Union and their correlation. Analytical, historical and generalizing methods, as well as a number of specific methods, such as historical-legal methods, were used during the following research. Սույն հոդվածը անդրադառնում է Եվրոպական Միությունում պետական ինքնիշխանության հիմնախնդրին։ Հետազոտության ընթացքում օգտագործվել են գիտական ուսումնասիրության վերլուծական, պատմական, ընդհանրացման մեթոդներ: Статья затрагивает вопрос государственного суверенитета в Европейском Союзе. В ходе исследования были использованы аналитические, исторические и обобщающие методы научного исследования.
Keywords: Social and Humanitarian Sciences